Best Alternatives Determination and Financial Feasibility Analysis of the Cleaner Production Application at Amplang Crackers Industry [Penentuan Alternatif Terbaik dan Analisis Kelayakan Finansial Penerapan Produksi Bersih Industri Kerupuk Amplang] - Kurnia Putri; Millatul Ulya; Umi Purwandari (Faculty of Fisheries and Marine Universitas Airlangga, 2019)
AbstractSmall-medium enterprises